Bandwidth enhancement of ultra-wideband monopole antenna designed with v-shaped defected ground structure - Lee Yee Hui; Dayang Azra Awang Mat; Dyg Norkhairunnisa Abang Zaidel; Kismet anak Hong Ping; Shafrida binti Sahrani Shahran (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
This paper discusses the design of a monopole antenna with various types of defected ground structures (DGS) for ultra-wideband (UWB) applications. The various types of DGSs are designed and acted as the ground layer of the antenna. The bandwidth of each design is then compared with and without the existence of DGS. Conventional monopole antenna has a bandwidth of 88.6% and operates in the frequency range of 3.1 to 8 GHz. According to the simulation results, the bandwidth of the monopole antenna with V-shaped DGS was the highest, which was at 133.3% (2.98-14.9 GHz), as compared to other types of DGS. The efficiency was between 30 to 64%, with a peak realized gain of 5.3 dB. The V-shaped DGS is then fabricated on a rogers RO4003C substrate with a relative permittivity, ????????, of 3.38 and a dimension of 29.86×39.03×0.81 mm. The antenna is measured using R&S network analyzer and the results were 3-8.5 GHz and 95.4% of BW, which signified the increased performance of the antenna.